An enhanced fast IP mobility management using multiple care–of–addresses in vehicular networks. (22nd May 2013) - Cho, Yeong–Hun; Chun, Seung–Man; Park, Jong–Tae
The IETF has developed the FMIPv6 which can be used for fast IP mobility management in vehicular networks. In the FMIPv6 protocol, if a prediction about a mobile node movement is incorrect, large handover delay may occur during handover operation. In this paper, we propose an enhanced fast IP mobility management, called EMIPv6, which can reduce both the handover latency and the packet loss in vehicular networks by utilising multiple Care–of–Addresses (CoAs) and the IEEE 802.21 Media Independent Handover (MIH) information service. The salient feature of the EMIPv6 is that multiple CoAs are, by extending the IETF FMIPv6 and the MIH information service, prepared in advance to reduce the movement prediction error of FMIPv6, thereby drastically reducing both handover latency and packet loss. Both mathematical analysis and simulation have been done for performance evaluation. The simulation results show that the EMIPv6 outperforms FMIPv6 in both handover latency and packet loss.